Design and applications of biocompatible choline amino acid ionic liquids. Issue 19 (16th September 2022) - Miao, Shurui; Atkin, Rob; Warr, Gregory
Abstract : ChAAILs are often used in mixtures to lower cost and improve handling, but the effects of water and other molecular additives are poorly understood. This review describes structure at different dilution stages and design strategies for task-specific ChAAIL-based mixtures. Abstract : Millions of tons of solvents are produced annually and are ubiquitous across many industries ranging from coatings, paintings, textiles, pharmaceuticals, extraction of resources, to chemical synthesis. The global market for solvents is projected to rise as solution processes are typically safer, more efficient, and easier to handle on an industrial scale. Therefore, the search and use of greener solvents are fundamental to our endeavour for a sustainable future. Ionic liquids (ILs) present exciting opportunities as next-generation solvents due to their designer characteristics and high recyclability. However, concerns remain around their toxicity and biocompatibility, and the cost of production is often high due to the low atom economy. Recently, ILs derived from biomolecules have emerged as biocompatible solvents with negligible toxicity and straightforward preparation. Choline amino acid ILs (ChAAILs) are a representative family of biocompatible ILs. They exhibit anion-controlled solvent properties and have been extensively studied for applications including biomass processing and CO2 capture. This review discusses the structure–property relationships of ChAAILs and their mixtures, especially with water. This lays the foundation for the rational design of ChAAIL-based solvent systems with optimised physical properties and reduced costs for specific applications.